The value of smart contracts in regulating foreign economic transactions - Kurbonova Mushtariy (Research Parks Publishers, 2021)
In this article, the author addresses the legal aspects of the conclusion of international agreements between the subjects of private law, in particular smart contracts. Systemic analyzes of private-level contracts based on the practice of German law and a number of other states, as well as on the basis of a comparative analysis method with a written form of contracts, positive and negative aspects of the nature of smart-contracts were revealed. The concluding opinions on the impact of smart contracts for foreign economic stability are given, and to the prospect of the individual relations of subjects in the Republic of Uzbekistan. In this article, the author addresses the legal aspects of the conclusion of international agreements between the subjects of private law, in particular smart contracts. Systemic analyzes of private-level contracts based on the practice of German law and a number of other states, as well as on the basis of a comparative analysis method with a written form of contracts, positive and negative aspects of the nature of smart-contracts were revealed. The concluding opinions on the impact of smart contracts for foreign economic stability are given, and to the prospect of the individual relations of subjects in the Republic of Uzbekistan.